PENGARUH MOTIVASI DAN PERCEIVED ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN DAN KINERJA DALAM STRATEGI PENINGKATAN KINERJA KARYAWAN (STUDI KASUS PT VALE INDONESIA Tbk) - Yanuar Putra; Muhammad Idrus Taba; Muhammad Sobarsyah (Hasanuddin Journal of Applied Business and Entrepreneurship, 2019)
For PT Vale Indonesia Tbk, performance is one of the important indicators for the company. Performance is also mentioned and described in the proceeds of the 2014 Joint Task Force which is the result of management agreements with trade unions as representatives of employees. To analyze the influence of motivation and perceived organizational support towards commitment and performance in employee performance improvement strategy at PT Vale Indonesia Tbk, used data collection technique through questionnaires distribution to selected employee as sample. Data analysis technique used in this research is Structural Equation Modeling (SEM) technique. This method is commonly used for the examination of relatively complex relations simultaneously with a sample of 202 people at PT Vale Indonesia Tbk. The results showed that commitment was positively and significantly influenced by Perceived Organizational Support and motivation, performance was positively and significantly influenced by motivation and Perceived Organizational Suppor, while commitment had positive and significant effect on employee performance at PT. Vale Indonesia Tbk, so the hypothesis in this research is accepted.